Investigation of Athletes' Habits of Playing Digital Game in The Pandemic Process - Tel, Mikail (Lahore Medical Research Center Llp, 2021)
Aim: In this study, athletes' views on digital games during the pandemic process were examined. Methods: x The sample of the study consists of 1521 (927 Male, 594 Female) athletes who continue their activities in different branches. The research is a screening model and has a descriptive quality. As a data collection tool, an online questionnaire form which questioned the demographic information of the participants, their frequency of playing digital games and the types of games they played was used. The SPSS package program was used to analyze the data and significance was accepted as p <0.05. Results: According to the results of the research, 60.9% of the participants were male, 35.5% were between the ages of 21-30, 59.2% were students and 61.5% were undergraduate and postgraduate athletes. When looking at the frequency of playing the game, 32.5% of them played with medium frequency. It was determined that athletes played games via a mobile phone at a higher rate than a desktop computer. In the answers given to the playing times during the pandemic process, yes was determined as 50.2%. Those who played 3 hours or more in daily playing time in pandemic were determined as 21.6%. In the pandemic, it was determined that the athletes played strategy, war, sportive games, backgammon-rummikub-chess, car racing and fighting games, respectively. Horror and role playing games were played at low rates. Considering the relationship between the age level of the athletes participating in the study and the types of the games, the rate of playing strategy games increased as the age got older, and young people between the ages of 21-30 played war games at higher rates. Internet usage rate of undergraduate and postgraduates of the participants was determined as 61.5%. Considering the educational status and the types of the games they played, it was determined that they played games such as strategy, war, sportive games and backgammonrummikub-chess at high rates. The higher the education level, the higher the rate of watching horror movies was. In addition, considering participants' sportive level and the types of games they played, it was determined that the trainers preferred sports and strategy games at higher rates. Considering the sportive level and the types of games played, it was determined that the athletes played games such as backgammon- rummikub -chess at lower rates. Conclusion: As a result; some changes were observed in athletes' lifestyles in the research group with the pandemic process, and the duration spent at home and playing games increased. In this context, it is considered that encouraging sports activities preventing inactivity at home during the pandemic process will positively affect the health of individuals.
Keywords: Pandemic; Game; Digital Games; Sports